N-heterocyclic carbene-catalyzed atroposelective annulation for access to thiazine derivatives with C-N axial chirality - Li, Tingting (2021)
A catalytic atroposelective cycloaddition reaction between thioureas and ynals is developed. This reaction features the first NHC-catalyzed addition of thioureas to acetylenic acylazolium intermediates to eventually set up C-N axial chirality with excellent optical purities. The obtained axially chiral thiazine derivative products bear multiple functional groups and are feasible for further transformations.